The Dynamics of Centralized Procurement Reform in a Decentralized State : Evidence and Lessons from Indonesia - Sacks, Audrey (World Bank Group, Washington, DC, 2014)
A central policy of the Government of Indonesia's strategy for enhancing its country's economic and social development is to develop infrastructure and expand service delivery. Public procurement reform is a key component of this policy. Despite the decentralization of financial responsibility and authority to relatively autonomous local level governments, procurement reform in Indonesia is a centrally-driven effort. In this paper, we examine the extent to which procurement reform is translating into improvements in sub-national performance. Data on local government procurement expenditures point to an overall decline in the volume of procurement, especially in poorer districts. This paper uses qualitative case studies of procurement reform in six local governments and finds that local government leadership is associated with the uptake of reform. There is little evidence to suggest that procurement reform has been "demand''-led, since neither the private sector nor Civil Society Organizations (CSOs) have been active in advocating for procurement reform.